2016
DOI: 10.1111/bph.13541
|View full text |Cite
|
Sign up to set email alerts
|

A novel plasminogen activator inhibitor‐1 inhibitor, TM5441, protects against high‐fat diet‐induced obesity and adipocyte injury in mice

Abstract: Obesity is one of the most prevalent chronic diseases worldwide, and dysregulated adipocyte function plays an important role in obesity-associated metabolic disorder. The level of plasma plasminogen activator inhibitor-1 (PAI-1) is increased in obese subjects, and PAI-1 null mice show improved insulin sensitivity when subjected to high-fat and high-sucrose diet-induced metabolic stress, suggesting that a best-in-class PAI-1 inhibitor may become a novel therapeutic agent for obesity-associated metabolic syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 47 publications
1
31
0
1
Order By: Relevance
“…A recent study showed that while overexpression/secretion of PAI‐1 led to premature aging in mice, the disruption of PAI‐1 production reversed this phenotype . Moreover, various disease states, such as cancer, cardiovascular disease, and diabetes, are also correlated with increased PAI‐1 expression and secretion . Therefore, developing ways to interfere with PAI‐1 function has been the focus of several groups since the establishment of its role in aging‐related diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study showed that while overexpression/secretion of PAI‐1 led to premature aging in mice, the disruption of PAI‐1 production reversed this phenotype . Moreover, various disease states, such as cancer, cardiovascular disease, and diabetes, are also correlated with increased PAI‐1 expression and secretion . Therefore, developing ways to interfere with PAI‐1 function has been the focus of several groups since the establishment of its role in aging‐related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…D (left) Western blot analysis was performed using whole-cell extracts from PRO cells, and antibodies specific for pRb (S795) and Rb proteins. cardiovascular disease, and diabetes, are also correlated with increased PAI-1 expression and secretion [68,76]. Therefore, developing ways to interfere with PAI-1 function has been the focus of several groups since the establishment of its role in aging-related diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PAI-1 belongs to a family of serine protease inhibitors, and an increased plasma PAI-1 level has been associated with insulin resistance (27). Knockout of PAI-1 suppresses weight gain in mice (28), and some pharmacological inhibitors of PAI-1 improve high fat diet-induced obesity in mice (29,30), indicating that inhibition of PAI-1 reduces adipogenesis. Although IL-8 increases the leptin secretion in human adipocytes (31), the effect of IL-8 derived from Caco-2 on fat accumulation in adipocytes is unclear.…”
Section: Discussionmentioning
confidence: 99%